Major acid endopeptidases of the blood-feeding monogenean Eudiplozoon nipponicum (Heteronchoinea: Diplozoidae) - Jedličková, Lucie; Dvořáková, Hana; Kašný, Martin; Ilgová, Jana; Potěšil, David; Zdráhal, Zbyněk; Mikeš, Libor (Parasitology, 2016)
In parasitic flatworms, acid endopeptidases are involved in crucial processes, including digestion, invasion, interactions with the host immune system, etc. In haematophagous monogeneans, however, no solid information has been available about the occurrence of these enzymes. Here we aimed to identify major cysteine and aspartic endopeptidase activities in Eudiplozoon nipponicum, an invasive haematophagous parasite of common carp. Employing biochemical, proteomic and molecular tools, we found that cysteine peptidase activities prevailed in soluble protein extracts and excretory/secretory products (ESP) of E. nipponicum; the major part was cathepsin L-like in nature supplemented with cathepsin B-like activity. Significant activity of the aspartic cathepsin D also occurred in soluble protein extracts. The degradation of haemoglobin in the presence of ESP and worm protein extracts was completely inhibited by a combination of cysteine and aspartic peptidase inhibitors, and diminished by particular cathepsin L, B and D inhibitors. Mass spectrometry revealed several tryptic peptides in ESP matching to two translated sequences of cathepsin L genes, which were amplified from cDNA of E. nipponicum and bioinformatically annotated. The dominance of cysteine peptidases of cathepsin L type in E. nipponicum resembles the situation in, e.g. fasciolid trematodes.
Keywords: cathepsin B; sekvenční seřazení; kathepsin L; Chromatography, Liquid; cysteine peptidase; sekvence nukleotidů; Tandem Mass Spectrometry; fish parasite; inhibitory proteas; Cathepsin D; Sequence Analysis, DNA; aspartic peptidase; endopeptidasy; Endopeptidases; Platyhelminths; cathepsin D; DNA, Complementary; cathepsin L; komplementární DNA; zvířata; cysteinové proteasy; peptidy; ploštěnci; Peptides; tandemová hmotnostní spektrometrie; sekvenční analýza DNA; Amino Acid Sequence; Cysteine Proteases; fluorescenční barviva; common carp; chromatografie kapalinová; Base Sequence; Fluorescent Dyes; kathepsin D; Cathepsin L; polymerázová řetězová reakce; Hydrogen-Ion Concentration; Sequence Alignment; Polymerase Chain Reaction; Cathepsin B; Animals; haematophagous monogenea; koncentrace vodíkových iontů; Protease Inhibitors; protease; sekvence aminokyselin; kathepsin B